2018
DOI: 10.3390/nu10030342
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Mouth Rinse Fails to Improve Four-Kilometer Cycling Time Trial Performance

Abstract: We investigated if a carbohydrate (CHO) mouth rinse may attenuate global fatigue and improve 4-km cycling time trial (TT4km) performance. After a preliminary session, cyclists (n = 9) performed a TT4km after a CHO or placebo (PLA) mouth rinse. Mean power output, time, and ratings of perceived exertion (RPE) were recorded throughout the TT4km. Twitch interpolation responses (%VA; voluntary activation and ∆Tw; delta peak twitch torque) were compared pre and post TT4km with traditional statistics and effect size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
3
14
0
5
Order By: Relevance
“…Se identificaron 96 publicaciones con las palabras clave y combinaciones en todas las bases de datos seleccionadas, se registraron 52 artículos duplicados, después de leer el título y el resumen se excluyeron otros 35 artículos. Los artículos restantes se leyeron a texto completo y se seleccionaron 7 artículos los cuales cumplieron con los criterios de inclusión y exclusión tal como se aprecia en la Figura 1 (22)(23)(24)(25)(26)(27)(28) .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Se identificaron 96 publicaciones con las palabras clave y combinaciones en todas las bases de datos seleccionadas, se registraron 52 artículos duplicados, después de leer el título y el resumen se excluyeron otros 35 artículos. Los artículos restantes se leyeron a texto completo y se seleccionaron 7 artículos los cuales cumplieron con los criterios de inclusión y exclusión tal como se aprecia en la Figura 1 (22)(23)(24)(25)(26)(27)(28) .…”
Section: Resultsunclassified
“…Por otro lado, Pires et al (22) concluyó que una intervención con glucosa no genera cambios significativos en el rendimiento TT y la fatiga a nivel central, sin embargo, sí genera efectos significativos en la fatiga a nivel periférico y potencia de salida, mientras que Devenney et al (26) reportó una mejora del rendimiento TT no asociada cambios significativos en la frecuencia cardiaca y percepción del esfuerzo. Esta diferencia en los resultados podría explicarse puesto que los principales moduladores de las respuestas centrales y periféricas en ejercicio son el volumen e intensidad de la carga, se sabe que intensidades de ejercicio bajas se correlacionan con una tasa de oxidación de glucosa baja, mientras que intensidades de ejercicio altas aumentan los requerimientos de glucosa y por ende el gasto energético generando una respuesta mucho más aguda en el reclutamiento muscular y el nivel de fatiga periférica las cuales pueden influenciar la potencia muscular y por ende el rendimiento en TT.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Indeed, in a recent study, we observed that CHO mouth rinse mitigated central fatigue during a 4 km cycling time trial, although being ineffective to enhance performance (likely due to a peripheral fatigue nature of this trial). 60 Accordingly, Bastos-Silva et al 61 verified beneficial CHO mouth rinse effects on a cycling-to-exhaustion test performance in intensity showing central rather than peripheral fatigue, that is low-to-moderate (80% of the respiratory compensation point) rather than high-intensity exercise (110% of the peak power output). Together, these studies 61 , 62 provided some support to the idea that CHO mouth rinse may be beneficial to improve performance mainly in exercise protocols that induce a central–peripheral fatigue interplay toward central limitations (i.e., moderate intensity, long duration).…”
Section: Type Of Exercise Protocolmentioning
confidence: 98%
“…Recently, plenty of research associates carbohydrate mouth rinse to positive effects in athletic performance, not only in endurance activities but also with a growing interest in high intensity sprint-based activities (1423). Recently, Brietzke et al (7) have reviewed the effects of carbohydrate mouth rinse on cycling time trial performance and they have concluded that this technique is effective in increasing cycling power output, although the magnitude of the effect was cataloged as “small.” Despite the overall positive effect of carbohydrate mouth rinse on cycling performance, all studies reporting no beneficial of carbohydrate mouth rinse on cycling performance tested participants in a fed state (2428). Although it seems that carbohydrate mouth rinse improved performance to a greater extent in a fasted compared with a fed state, the use of fasting prior to exercise might not be an optimal choice to maximize cycling performance.…”
Section: Introductionmentioning
confidence: 99%